AQUANOVA as an innovation in thermosaline otec-pro power generation technology based on anfis-fuzzy logic for optimizing sustainable air quality - Ainun Jariyah; Sela Elfina (Journal of Innovation Materials, Energy, and Sustainable Engineering, 2026)
Background: In 2024, the Meteorology, Climatology, and Geophysics Agency reported that the average global temperature had exceeded the threshold of 1.5°C compared to the pre-industrial era. The rate of global warming is caused by the greenhouse gas (GHG) effect, which is dominated by carbon dioxide. The increase in atmospheric temperature is caused by CO2 from carbon emissions from the use of fossil energy sources, land conversion, and deforestation. This study examines technologies that can be used to optimize air quality and the types of renewable energy that can be integrated into air quality optimization technology designs. Methods: The methodological approach chosen in this study is a Systematic Literature Review (SLR). Data searches were conducted on several websites using the keywords “global warming,” “CO2 levels in Indonesia,” and “power generation technology.” Findings: Based on these issues, AQUANOVA was developed as an innovative air purification technology that can absorb CO2 in the atmosphere and be integrated with OTEC, PRO, and air purifiers to reduce carbon emissions in the air. Conclusion: This study developed the AQUANOVA innovation as a technology that can reduce CO2 emissions based on ANFIS-Fuzzy Logic management as an effort to achieve SDG points 7 and 15 in producing affordable renewable energy and restoring ecosystems. Novelty/Originality of this article: The integration of two electricity-generating technologies and the ANFIS-Fuzzy Logic automation system has created an innovative automatic and energy-efficient air purifier technology.